Methylphenidate decreases fat and carbohydrate intake in obese teenagers. (3rd December 2013) - Danilovich, N.; Mastrandrea, L.D.; Cataldi, L.; Quattrin, T.
<x xml:space="preserve">Abstract</x> Objective Dopamine is a neurotransmitter that mediates the reward value of food. Methylphenidate (MPH) selectively binds and inhibits the dopamine transporter, thus increasing brain dopamine levels shortly after oral administration. This investigation studied whether a single dose of MPH decreases energy intake (EI) in obese teenagers compared to placebo (P). Methods This study used a single‐blind, placebo‐controlled, within subject design. Teenagers with body mass index (BMI) ≥95th percentile underwent two identical meal tests (P or MPH) after a 10 h fast in random order. Food was weighed before and after the meals, and EI was calculated as energy content/gram of consumed foods. Total and macronutrient EI (mean ± SD) were analyzed by Mann–Whitney U and Wilcoxon tests. Results Twenty‐two subjects (15 females, 7 males) completed the study. Participants were 13.4 ± 2.2 years old and had BMI 34.9 ± 10.7 kg/m². EI from fat (167 vs. 203 kcal, P = 0.03) and carbohydrates (311 vs. 389 kcal, P = 0.04) was decreased for MPH compared to P meals, with a trend in decreased total EI (545 vs. 663 kcal, P = 0.06). Conclusion A single dose of MPH decreases EI from fat and carbohydrates in obese adolescents. This effect underscores the importance of central dopamine signaling on eating behavior.